Politik Hukum yang Berorientasi pada Administrasi Kelautan dan Kemaritiman - Endri Endri (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2019)
AbstractThe purpose of this study is to find out the politics of law, which is oriented to maritime and maritime administration. The writing method is a writing proposal, which is analyzed using qualitative analysis. The results of the research show that legal politics in the direction of development that will be achieved by the Indonesian state. As a state of law and as an archipelago, the legitimate politics of the Indonesian people are not yet fully oriented towards maritime and maritime affairs. Some regulations which are bound with naval affairs and naval affairs are not effective in law enforcement so that they need to be improved or revised, but they are not included in the legislation program. While the legislation programs that have been set up, there are still some that have not been achieved, especially regarding maritime affairs and maritime affairs.Keywords: Maritime Administration, Political Law, Indonesia. AbstrakTujuan kajian ini adalah untuk mengetahui politik hukum yang berorientasi pada administrasi kelautan dan kemaritiman. Metode penulisan adalah penulisan hukum yang dianalisis menggunakan analisis kualitatif. Hasil penelitian menjukan bahwa politik hukum merupakan arah pembangunan yang akan dicapai oleh negara Indonesia. Sebagai negara hukum dan sebagai negara kepulauan, politik hukum bangsa Indonesia belum sepenuhnya berorientasi pada kelautan dan kemaritiman. Beberapa peraturan yang terikat dengan kelautan dan kemaritiman tidak efektif dalam penegakan hukum sehingga perlu perbaikan atau revisi akan tetapi tidak masuk program legislasi. Sedangkan program legislasi yang telah ditetapkan pun masih ada yang belum tercapai khususnya tentang kelautan dan kemaritiman.Kata Kunci: Administrasi kelautan, Politik Hukum, Indonesia.